La producción escrita en inglés mediante el "blogging" en un entorno de aprendizaje basado en proyectos en bachillerato - Montaner Villalba, Salvador (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
In this paper, we analyze Blogging as a tool to promote written production in English as a Foreign Language within a Project-Based Learning approach. Two research questions were set up in order to study whether learners’ level in their EFL written production improved. Quantitative data were collected and analyzed within an Action-Research methodology. Blogs were used in the 1st academic year at A-level and thus in post compulsory secondary education. The students had a B1 level (according to the European Framework of Reference for Languages). The outcomes confirmed the hypothesis and students improved their written performance.